Penyesuaian Norma Global di Asia Tenggara: Konsep Adopsi Parsial Dalam Lokalisasi Responsibility to Protect Dalam Krisis Humaniter Myanmar 2008 - Mahardika, Asyifa; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Debate over Responsibility to Protect in ASEAN has not reached any consensus up until now. This is caused by a clash between Responsibility to Protect and ASEAN Way. Some argues that Responsibility to Protect is applicable in ASEAN, while the rest thinks otherwise. By using norm localization as part of constructivism, this research aims to give a brand new notion that Responsibility to Protect might be applied partially in ASEAN. A case of study about Myanmar humanitarian crisis in 2008 serves a set of implicit yet explicit proves on how Responsibility to Protect can be applied in ASEAN. Data were collected using literature study and official documentaries, and analyzed using causal-process tracing. The result of this research shows that ASEAN had penetrated all steps in Responsibility to Protect localization. Although the final step isn’t perfectly done yet, ASEAN is proved to be receiving the main principal of Responsibility to Protect